Engaging elite support for the poorest? BRAC's experience with the ultra poor programme (TUP working paper -3) - Hossain, Naomi; Matin, Imran (BRAC, 2019)
This paper describes and draws lessons from the experience of engaging village elite in support of the ultra poor through the Gram Shahayak Committees (GSC), as part of BRAC's CFPR/TUP programme. The paper addresses the following questions: under what conditions can elite become engaged in support of interventions for the ultra poor? What are the risks and benefits of engaging elite in antipoverty programmes? After describing the origins and motivations behind BRAC's Specially Targeted Ultra Poor (TUP) programme, the paper goes on to explain how an important lesson from the programme as it evolved included the need for on-site, village-based protection and support for TUP participants and their newly-acquired assets. The paper goes on to explore some of the early impacts of the GSCs which were formed to fill this need, and to assess the motivations and factors underlying their effectiveness and success. The paper concludes with a brief discussion of the lessons from the experience, including their implications for assumptions that dominate scholarship and programmes relating· to the rural politics of poverty in Bangladesh.